Proses Pemeriksaan Tindak Pidana Pemalsuan Surat Genose Pada Masa Pandemi Covid-19 - Gabriel Makatita; Reimon Supusepa; Judy Marria Saimima (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Forgery of letters is caused by unauthorized changes ( without valid permission ) to letter or documents.Threats to trevelers if they are found to have falsified a covid-19 free certificate with the aim of traveling in the midst of the covid-19 outbreak.Purposes of the Research: The purpose of the current study is to analyze and  discuse how the process of forgery of letters during the covid-19 pandemic can be classified as a criminal act of forgery of letter, as regulated in article 263 of the criminal code. Methods of the Research: The research method in this study is a noemative research, using a law approach and a conceptual approach. research data sources include primary, secondary, tertiary legal sources. Data collection techniques in the from of literature study. Processing and analysis of legal material used in writing is using qualitative analysis methods.Results of the Research: The result of the research show that the criminal act of forging letters as referred to in article 236 of the criminal code, which was found on Thursday 27 May 2021, around 18:30 WIT at one of the Travel Agents PT. Laperissa Chaur on Ay Patty  street, Ambon City. There were individuals who faked the GoNose covid-19 letter, the letter was made and assisted by suspect Rusrman, Husni Suatrean alias Nyong, Mahmudin alias Udin, and Rizky Nuralini Rizdianto alias Iki.